ANTIBIOTIC RESISTANCES OF MARINE BACTERIA FROM HON MOT, NHA TRANG BAY - Mien, Pham Thi; Ha, Dao Viet; Hanh, Nguyen Kim (Vietnam Journal of Marine Science and Technology, 2018)
Drug resistance is now an issue of deep scientific concern all over the world as more antibiotic resistant bacteria have been detected in many regions and countries in recent years. Using of antibiotics for aquaculture is quite common in developing countries including Vietnam. This causes the spread of antibiotic resistant bacteria in the environment. Testing of antibiotic resistant bacteria was carried out in commercial marine aquaculture and tourist zones in Hon Mot in the Nha Trang bay with five different antibiotics namely chloramphenicol, tetracycline, cefazolin, streptomycin, and gentamicin on Mueller Hinton Agar. A total of 18 strains composed of 14 Gram positive strains, 4 Gram negative strains were tested for antibiotic resistance. Strain KH1 showed the least sensitive to tetracycline with average radius of 4.0 mm, while strain T1 showed the least sensitive to streptomycin with average radius of 4.2 mm. The strains KH6 and T7 showed resistance to cefazolin with radius of inhibition zone of 0 mm and 2 mm, respectively. The strain KH6 was confirmed as Bacillus sp. Antibiotic resistant bacteria were now found in Nha Trang bay, so there may be additional resistant bacteria, even multi-antibiotic resistant bacteria outside the marine environment. This is a matter for further research that should provide solutions to limit the rise of antibiotic resistant bacteria.